EKSPLORASI KERAGAMAN MORFOLOGI TANAMAN JAHE (Zingiber officinale Rosc.) LOKAL DI KABUPATEN LEBAK, PROVINSI BANTEN - Marwah Nurfadilah; Andi Apriany Fatmawaty; Nur Iman Muztahidin; Alfu Laila; Fajar Dwi Prasetyo (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2021)
Lebak is a district in Banten province known as one of center for ginger cultivations. The study aimed to determine the diversity of local ginger plants in Lebak-Banten Regency based on morphological characters, so that kinship relationships between commodities can be seen. The study was conducted from Agustus to October 2021. This study used qualitative and quantitative descriptive methods, consisting of 7 accessions with a total sample of 21 plants from the districts in Lebak Regency as Panggarangan, Malingping, Banjarsari and Gunung Kencana. The data was processed using SPSS. Based on the results, there were 7 similar qualitative characters and 3 different qualitative characters. While there were 8 board quantitative characters (various) and 1 narrow quantitative character (uniform), the closest kinship relationship is found in accessions (B3 and E1) with a coefficient value of 1.576 and the furthest kinship in accessions (A1 and D3) wit a coefficient value of 51.024. The results of the dendogram showed that on a scale of 5 formed 14 groups, on a scale of 10 formed 7 groups, a scale of 15 formed 4 groups, a scale of 20 formed 3 group and a scale of 25 formed 2 group. Therefore, further research is needed to determine the relationship of the local ginger based on molecular analysis.